Exploring the impact of strategic management accounting on firm competitiveness in Zimbabwe - Munyepwa, Kudakwashe; Ranganayi, Charity; Mudzengerere, Liberty; Mutongereni, Noah; Gwesu, Norah Chishamiso; Machaka, Tafadzwa Hatidani (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study investigates the role of Strategic Management Accounting (SMA) in enhancing competitive advantage in Zimbabwean firms, focusing on the Balanced Scorecard (BSC), Activity-Based Costing (ABC), and Value Chain Analysis (VCA). Methodology: A mixed-methods design was employed. Qualitative data were collected through semi-structured interviews with 15 senior managers from manufacturing, financial services, and technology sectors, exploring SMA integration in strategic decision-making. Quantitative data were gathered via a survey of 100–150 medium and large enterprises, examining SMA adoption and performance impacts. Regression modelling and factor analysis assessed relationships between SMA implementation and performance indicators such as profitability, customer satisfaction, innovation, and cost efficiency. Results: The Balanced Scorecard improved strategic coherence and performance monitoring. ABC enhanced cost transparency and resource utilisation, while VCA offered insights into strategic positioning and value creation. Combined, these tools fostered strategic responsiveness, operational efficiency, and continuous improvement, positively influencing both financial and non-financial outcomes. Conclusions: SMA tools significantly support competitive advantage in Zimbabwean firms by aligning strategy, improving decision-making, and enhancing performance. Systematic integration strengthens both strategic management and performance measurement processes. Limitations: The study focused on select sectors and relied on managerial perceptions and self-reported survey data, limiting generalisability and introducing potential bias. Contributions: This research empirically validates the performance-enhancing role of SMA tools in a Zimbabwean context and provides a practical framework for integrating SMA into strategic management, demonstrating the value of a mixed-methods approach for understanding adoption and impact.